The impact of mutant alsin protein on motor neuron models and the effects of alsin gene knock-down on motor protein genes - Lahut, Suna. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
Alsin is a ubiquitously expressed protein with the highest levels in the central nervous system. Mutations in the alsin gene have been associated with several juvenile onset recessive motor neuron diseases. Nine out of 12 reported mutations in the alsin gene are deleterious mutations, leading to premature termination of the protein by an early stop codon; all affected patients are homozygous and all unaffected siblings are heterozygous or normal for the alsin mutations. These together, suggest a loss of function mechanism, responsible for motor neuron degeneration. The aim of this study is to understand the function of alsin using two different approaches. The first approach investigates the effects of mutant alsin on cells with motor neuron characteristics. The alsin mutation generated in this study leads to the truncation of one third of the protein, including the VPS domain, as it is the case in the majority of the natural mutations. The second approach analyzes alsin’s possible interactions with six motor proteins, which have a role in axonal transport: DCTN1, DCTN2, DCTN3, KIF3A, KIF3B and KIF5A. The results of this thesis suggest a rapid degradation of the mutant alsin protein in the NSC34 cells. Thus, it concludes that the pathogenesis of ALS might be due to the overall loss of the alsin protein rather than the loss of the VPS domain, as reported before in the literature. This study also implicates a possible interaction of alsin with three of the six investigated proteins: DCTN1, KIF3A and KIF3B. It further shows a co-localization of alsin and KIF3A in the perinuclear region of N2a cells. This thesis is a first attempt in our laboratory for elucidating the alsin-interacting partners in cell culture systems; we hope that this study will help to pave the ways for understanding the complicated and multilayered functions of the alsin protein.
Keywords: Amyotrophic lateral sclerosis.; Central nervous system -- Diseases